Towards a theoretical framework for the innovation in sustainability reporting: An integrated reporting perspective - Sun, Yanqi; Davey, Howard; Arunachalam, Murugesh; Cao, Yuanyuan (Frontiers in Environmental Science, 2022)
Integrated Reporting (IR), as a novel sustainability-oriented organizational reporting approach, is expected to produce better corporate reporting for stakeholders and promote greater transparency and accountability in the capital market. This paper offers a theoretical framework that integrates five mainstream IR theories: stakeholder theory, agency theory, signalling theory, legitimacy theory, and institutional theory. Based on the theoretical framework, there are three drivers for companies to improve their IR disclosure practices: to mitigate information asymmetry between the organisation and all stakeholders; to signal superior quality, legitimacy, and conformity to all stakeholders; and to discharge accountability to all stakeholders. Direct and indirect costs are the main factors that lead to poor IR disclosure practices. This study is the first attempt to construct an integrated theoretical framework for IR. The constructed framework can be adopted as a theoretical foundation for future empirical studies with regard to IR.